UTILIZATION OF WOODEN PLANTS AS A RAW MATERIAL SHIP BOCAI VILLAGE SANDBALL VILLAGE SUNGAI LALA DISTRICT INDRAGIRI HULU - Assodiqi Hidayatullah; Evi Sribudiani; Sonia Somadona (Jurusan Kehutanan Fakultas Pertanian Universitas Riau, 2021)
Bocai is a traditional ship which originated from Pasir Bongkal Village, Sungai Lala District, Indragiri Hulu Regency. The type of size of the kid in the sandstone village is very diverse, because the kid is used for several purposes. Distinctive characteristics of the leak can be seen on the front and rear of the blunt, called the threshold, in addition to the characteristics of the hull shape or often referred to as the body of the ship is not fat and wide. In connection with this, research on the use of woody plants as raw material for Bocai vessels in the Sand Bongkal Village, Sungai Lala District, Indragiri Hulu District. The selection of informants was made to shipbuilders and shipowners, using the Purposive Sampling technique. The implementation of this research is divided into several techniques, namely observation and interviews, observations made in this study in the form of data and information consisting of primary and secondary data. The data analysis technique used is the qualitative descriptive analysis method, in the form of woody plant species used by the Sand Bongkal Village community and how to use them. The types of wood that are used in making the ship Bocai Sand Bongkal Village are bungur, cempedak, durian, rengas, red meranti, keruing, and kulim. The technique of making a ship ship first install keel then log, ambang, gading-gading, gading kong, papan, tajuk, pisang-pisang, sente, nage-nage, pulang, dek, pemakalan, gale-gale.